Radical absorption of dihydrostreptomycin sulafto by Phaseolus vulgaris in hydroponic cultures. Its influence on the inhibition of the experimental pathogenic power of Pseudomonas savastanoi for said plant - Romero, P.; Callao, V.; Henares, M. (Ars Pharmaceutica (Internet), 1970)
In this paper the nutritive solution and technique for cultivation of Phaseolus vulgaris in hidroponic media are given; the methods for valoration of dihidrosteptomicina silphate and the results obtained  in the absorption of this antibiotic have also indicated. It has been concluded that under the conditions of experimentation carried out, the experimental infection of Ph. vulgaaris by Ps. savastanoi (strain 64) is not inhibited by the action of the antibiotic used.